Use of Laparoscopic and Laparotomic J-Plasma Handpiece in Gynecological Malignancies: Results From A Pilot Study in A Tertiary Care Center - Gueli Alletti, Salvatore; Rosati, Andrea; Capozzi, Vito Andrea; Pavone, Matteo; Gioè, Alessandro; Cianci, Stefano; Chiantera, Vito; Vizzielli, Giuseppe; Scaglione, Giulia; Fagotti, Anna; Scambia, Giovanni (Frontiers in Oncology, 2022)
Introduction The J-Plasma has recently been introduced into the surgical community with different intrinsic characteristics aimed to further reduce the thermal effect and enhance precision when compared to standard radiofrequency. This study aimed to investigate the role of this new technology in different conditions of gynecological carcinomatosis characterized by the indication for regional peritonectomy and/or ablation, either in laparotomy (LPT) or in laparoscopy (LPS), in the context of a modern personalized approach to the surgical management of gynecological malignancies. Material and Methods From January 2019 to April 2019, 12 patients were selected for this prospective pilot study at the Division of Gynecologic Oncology, Fondazione Policlinico Universitario A. Gemelli IRCCS in Rome. In this single surgeon experience, the inclusion criteria were: histologically proven advanced ovarian/endometrial cancer, primary or interval debulking surgery, and intraoperative indication for regional peritonectomy. Six patients were treated by LPS (Group 1) and 6 by LPT (Group 2). Results In Group 1 the indication for debulking surgery was in 4 cases an interval debulking surgery and 2 advanced endometrial cancer. All patients in Group 2 underwent primary debulking surgery for advanced ovarian cancer. The whole cohort achieved a complete tumor excision after surgery. The median OT and median EBL were 195 min and 100 ml in Group 1, and 420 min and 500 ml in Group 2. The median hospital stay was 4 days in Group 1 and 13 days in Group 2, respectively. No intra and postoperative complications were registered within 60 days after surgery. Conclusions J-Plasma allows to approach delicate maneuvers on viscera, mesentery, and blood vessels with a high degree of safety and precision thanks to its limited vertical and lateral thermal spread, favoring the surgeon to push ever higher the cytoreduction/morbidity tradeoff. The use of J-Plasma in cytoreductive surgery could also increase the range of possible minimally invasive procedures, narrowing the technical distance with the open technique and thus contributing to designing a personalized surgical strategy for each patient in different scenarios of peritoneal carcinomatosis.